Anxiety and Depression Among People Under the Nationwide Partial Lockdown in Vietnam - Le, Huong Thi; Lai, Andre Jun Xian; Sun, Jiaqian; Hoang, Men Thi; Vu, Linh Gia; Pham, Hai Quang; Nguyen, Trang Ha; Tran, Bach Xuan; Latkin, Carl A.; Le, Xuan Thi Thanh; Nguyen, Thao Thanh; Pham, Quan Thi; et al. (Frontiers in Public Health, 2020)
This study aimed to evaluate the psychological effects of the partial lockdown on the people in Vietnam during the COVID-19 pandemic. An online questionnaire regarding attitudes towards COVID-19 along with psychological parameters, including the Impact of Event Scale-Revised (IES-R) Depression, Anxiety, Stress Scale-21 (DASS-21) was conducted. From a total of 1382 questionnaires, the respondents reported low prevalence of depression (4.9%), anxiety (7.0%), and stress (3.4%). The mean DASS-21 scores recorded were also markedly lower compared to similar studies conducted in China, Italy and Iran. Respondents who reported severe PTSD had significantly higher depression, anxiety, and stress levels. Factors that were associated with an increased level of depression, stress and anxiety were being single, separated or widowed, a higher education level, a larger family size, loss of jobs and being in contact with potential COVID-19 patients. Contrary to expectations, the level of depression, stress and anxiety observed has been low. Our findings can aid in future research on the impact of a partial lockdown and guide mental health professionals in Vietnam and other countries in the preparation of better care for populations under such circumstances.